Integration of local wisdom values in the formation of attitudes of elementary school student: Systematic literature review - Dhiyaa Najmii Fitrianti; Mela Darmayanti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study examines the integration of local wisdom values in shaping the attitudes of elementary school students through a systematic literature review of 41 articles published between 2021 and 2025, using the PRISMA 2020 protocol. Bibliometric analysis with VOSviewer and thematic analysis were employed to identify research trends and synthesize key findings. The results reveal a notable increase in publications during 2024–2025, with qualitative methods predominating. Local wisdom emerges as the core concept, structured into five thematic clusters. Six effective strategies for implementation are identified: thematic learning, integration of local content, innovative learning models, culture-based learning media, routine habituation, and the P5 (Projek Penguatan Profil Pelajar Pancasila) program. The dominant character values fostered include mutual cooperation, responsibility, and tolerance, reflecting Indonesia’s cultural plurality. The novelty of this study lies in its integrative approach, combining bibliometric and thematic analyses to comprehensively map research on local wisdom-based character education within the framework of the Pancasila Student Profile. This approach provides an updated synthesis that extends beyond prior reviews, which tended to focus on descriptive findings without systematic mapping. Moreover, the review identifies important research gaps, particularly the limited use of experimental and mixed-method designs, which constrains the strength of causal evidence regarding the effectiveness of local wisdom integration. From a practical perspective, the findings offer relevant implications for basic education policy and practice. These include the development of context-based learning modules grounded in local wisdom, targeted teacher training to strengthen pedagogical and cultural competencies, and enhanced collaboration among schools, communities, and local governments. Addressing these aspects is crucial to overcoming challenges related to teacher capacity, limited resources, and globalization pressures, thereby optimizing character education and supporting the sustainable realization of the Pancasila Student Profile in elementary schools.